Stress, trauma, and wellbeing in the legal system - Miller, Monica K.; Bornstein, Brian H. (New York : Oxford University Press, 2013)
This title presents theory, research, and scholarship from a variety of social scientific disciplines and offers suggestions for those interested in exploring and improving the wellbeing of those who are voluntarily or involuntarily drawn into the legal system.
Series from CIP print record.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Includes bibliographical references and index.
Keywords: Justice, Administration of -- United States -- Psychological aspects; Stress (Psychology) -- United States; Therapeutic Jurisprudence -- United States